PENGARUH LATIHAN INTERVAL TRAINING TERHADAP DAYA TAHAN ATLET LARI 1500 METER ATLET ATLETIK PROVINSI RIAU - Indra Bakti Panjaitan; Slamet Slamet; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstark: The problem in this research is that athletes who don't perform well in running techniques tend to tire quickly. The title studied in this research y was "The Effect of Interval Training on the Endurance of Athletes Running 1500m for Athletics in Riau Province". The purpose of this research was to determine whether athletic athletes' stamina increases. The format of this research is to use a one-group pretest-postest design approach with a population of athletic athletes in Riau province. The data in this research refers to the entire population of 8 subjects. The tool used in this research was to use a bar test, which aims to determine how long the athlete's endurance has. To test for normality using the Lilifours test at a significant level of 0.05α. Based on the analysis of the normality test, the data X gives a LoMax of 0.250 and an L table of 0.285, while variable Y gives a LoMax of 0.254 and an L table of 0.285. This means that LoMax <Ltable, then the data will be distributed normally. Based on statistical data analysis, there is an average of variable X 51.41 and an average of variable Y of 51.61 for the t-distribution test of the effect between variable x and variable y, the value of t = 4.751 is obtained , and then tcount> t-table, namely (4,751)> (1,895), then Ha is accepted, in other words, there is an effect of interval training on the endurance of athletes running 1500 meters in athletics in Riau province.Key Words: Interval Training, Endurance